Evaluation of screw placement in proximal humerus fractures regarding drilling manoeuvre and surgeon's experience. (September 2021) - Hohenberger, Gloria Maria; Schwarz, Angelika Maria; Dauwe, Jan; Grechenig, Peter; Staresinic, Mario; Feigl, Georg; Bakota, Bore
Highlights: The aim was to determine the influence of surgeons' experience and the technique of drilling on the complication rate. The perforation rate of the articular cavity ranged from 3.4% to 5.2%. There were no statistically significant differences regarding drilling manoeuvres nor experience. Abstract: Introduction: Following proximal humeral plate osteosynthesis, mechanical complication rates ranging up to 40% have been reported. The study aims to determine the influence of surgeons' experience and the technique of drilling on the complication rate. Materials and Methods: The sample involved 45 cadaveric humeri. Six orthopaedic surgeons were divided into two groups with regard to their level of experience (novice versus expert group). On each humerus two different proximal humerus plates were applied. Drillings were performed either with a sharp or worn drill bit (to simulate either sharp or blunt drilling). The respective holes were drilled until the respective participant thought to have placed the drill bit subchondrally, followed by perforation of the cartilage of the humeral head. Both these values and cases of unintended penetration of the articular cavity were evaluated. Results: Fourteen holes (3.6%) were primary penetrated in the joint cavity in the worn-drill-bit-subgroup and 19 holes (5%) in the sharp-drill-bit-group. The latter had an average distance between the chosen subchondral position and the humeral articular surface of 8.3 mm and the worn-drill-bit-subgroup was at 10.6 mm. In the novice group 20 perforations (5.2%) of the joint space occurred and the mean interval between the chosen subchondral point and the humeral articular surface was 4.0 mm. The experienced surgeons showed a perforation rate of 3.4% and were at a mean of 14.9 mm. There were no significant differences regarding drilling manoeuvres and experience. Conclusion: Although our results are satisfactory, they can be traced back to the relatively high interval between the respective chosen position of the drill bit and the humeral articular surface which may not guarantee screw stability during ORIF of all fracture patterns.